Improving Learning Outcomes Through Make and Match Learning Model for Class 1 SDN Kedunguter 02 Brebes - Eti Sarwoniroh (Universitas Sebelas Maret, 2020)
The purpose of this study is to improve the learning outcomes of students in first grade elementary school with the Make And Match learning model. The research was a two-cycle Class Action Research (PTK), with each cycle consisting of two meetings. The stages of each cycle are planning, implementation, observation and reflection. Each meeting is conducted pre test and Post test to know the development of students. In cycle I students completed after doing post test by 76%. In cycle II students who completed after carrying out the post test by 92%. These results show that the Make And Match learning model can improve the learning outcomes of students at SD Negeri Kedunguter 02 Brebes.